A correlation-based inversion method for aerosol property (CIMAP) retrieval from AERONET measurements. (September 2021) - Huang, Taozhong; Xu, Feng; Gao, Lan; Flynn, Connor J.; Dubovik, Oleg
Highlights: A correlation-based inversion approach is developed for an efficient retrieval of aerosol properties in a significantly reduced parameter space. Algorithm is tested using AERONET instrument data. Comparison to AERONET reference data shows similar accuracy. Abstract: We developed a principal-component based inversion approach – CIMAP, to retrieve aerosol properties from AERONET measurements of aerosol optical depths (AODs) and sky radiances. Capitalizing on the correlation in aerosol properties, CIMAP reduces the aerosol retrieval parameter space and saves retrieval time by more than 80% from adopting 7-8 principal components in the retrieval process, compared to retrievals in regular parameter space. As algorithm test, CIMAP is implemented to retrieve 60 sets of AERONET observations in several selected areas in southern California, southern Africa, and north China around Beijing, and the results are compared to the AERONET measurement and operational retrieval products. The mean absolute differences are found to be 0.004, 0.019, 0.032, 0.039, 0.003 and 0.044µm for AOD, single scattering albedo, Ångström exponent, real and imaginary parts of refractive index and effective radius of aerosols, respectively. These differences are within or close to AERONET measurement or retrieval uncertainties.